1990
DOI: 10.1093/nar/18.3.513
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus and minute virus of mice DNAs are localized at the nuclear periphery

Abstract: The localization of adenovirus 2 (Ad2) and Minute Virus of Mice (MVM) DNAs was studied in situ in infected HeLa cell nuclei using fluorescent DNA probes and confocal microscopy. Ad2 DNA was found in multiple foci which were localized along the periphery of the infected cell nuclei. MVM DNA was found in HeLa cell nucleoli which are associated with the nuclear envelope, and when co-infected with Ad2 MVM DNA was compartmentalized to multiple foci which again were localized at the nuclear periphery. The data are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
14
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…Thus, the E1B transcription unit is exposed to a different population of trans-regulatory factors early versus late after infection. Recent electron microscope work has localized adenovirus DNA in the late phase to discrete foci or 'replication factories' in the nucleus (Moen et al, 1990) and thus one could postulate that two templates in the same cell can be in separate nuclear compartments. Several groups have shown that adenovirus DNA is linked tightly to the nuclear matrix throughout infection and that this linkage is important for viral transcription and replication (Bodnar et al, 1989;Schaack et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the E1B transcription unit is exposed to a different population of trans-regulatory factors early versus late after infection. Recent electron microscope work has localized adenovirus DNA in the late phase to discrete foci or 'replication factories' in the nucleus (Moen et al, 1990) and thus one could postulate that two templates in the same cell can be in separate nuclear compartments. Several groups have shown that adenovirus DNA is linked tightly to the nuclear matrix throughout infection and that this linkage is important for viral transcription and replication (Bodnar et al, 1989;Schaack et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have shown that adenovirus DNA is linked tightly to the nuclear matrix throughout infection and that this linkage is important for viral transcription and replication (Bodnar et al, 1989;Schaack et al, 1990). Recent electron microscope work has localized adenovirus DNA in the late phase to discrete foci or 'replication factories' in the nucleus (Moen et al, 1990) and thus one could postulate that two templates in the same cell can be in separate nuclear compartments. Additionally there is evidence that not only transcription but also processing of mRNA is believed to occur on the nuclear matrix and in discrete places (Lawrence et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The NM is involved in many important cellular activities, such as transcription, mRNA splicing, mRNA transport, chromatin organization, and DNA replication (6,28,35,49). Therefore, it is not surprising that sites of Ad replication and transcription are discretely localized to foci in the nuclear substructure (11,37). The interaction of Ad pTP with the NM may link these cellular processes with the viral life cycle.…”
mentioning
confidence: 99%
“…AAV-2 then uses the cellular replication factors and factors involved in RNA transcription and processing recruited to these centers for its own propagation. Interestingly, the genome replication of the autonomous minute virus of mice (MVM) is increased strongly by Ad2 infection in HeLa cells (15) accompanied by a recompartmentalization of the MVM DNA from the nucleolus to the adenoviral replication centers (15,33). In contrast to the situation with B19V, however, 293 cells are able to replicate MVM DNA quite efficiently in the absence of adenovirus, and no extra stimulation is observed by providing additional adenoviral functions, although recompartmentalization of the MVM DNA is also observed (15).…”
Section: Discussionmentioning
confidence: 99%